Analisis dan Perencanaan Strategis SI/TI pada PT KCIC - Septiana, Nana; Albarri, Rifqi Alwan; Rahmatullah, Muhammad Iqbal; Darwis, Muhammad (INTERNAL (Information System Journal), 2024)
This study aims to investigate the impact and challenges of the implementation of Information Systems (SI) and Information Technology (IT) in the construction environment of PT KCIC (Kereta Cepat Indonesia China). This study explores the implementation of SI and IT in PT KCIC using various strategic management analysis methods, including Business Model Canvas (BMC), SWOT Analysis, PEST Analysis, and the Ward and Peppard framework. Through this multidimensional approach, this research aims to investigate the impacts and challenges of IS and IT implementation in the PT KCIC construction environment. Data was collected through surveys, interviews, and analysis of company documentation. BMC is used to understand PT KCIC's business model, while SWOT and PEST are used to analyze the internal and external environment. The Ward and Peppard method is used to develop IS and IT implementation strategies that suit the company's needs and challenges. The research results highlight the importance of IS and IT integration in PT KCIC's business strategy, as well as the challenges faced in process implementation, such as data security, IT infrastructure, and the adequacy of activated human resources. This research provides in-depth insight into how PT KCIC can optimally utilize IS and IT to increase its operational efficiency and effectiveness.